Effectiveness of Computer Animation Instructional Package on Academic Achievement of Senior Secondary School Agricultural Science Students in Animal Physiology in Minna, Nigeria - O.C. Falode; M.F. Sobowale; R.M. Saliu; H. Usman; M.E. Falode (University of Sofia, 2016)
The study was carried out to determine the effectiveness of Computer Animation Instructional Package (CAIP) on academic achievement of senior secondary school agricultural science students in animal physiology in Minna, Nigeria. Influence of gender was also examined. Quazi-experimental procedure of pretest, post-test, and non-randomized, non-equivalent design was adopted. Two research questions were raised while two null hypotheses were tested at 0.05 level of significance. The sample of the study was made up of 88 senior secondary school students selected from intact classes of two co-educational public schools within the study area. The two schools were randomly assigned to experimental and control groups. The experimental group which comprised 48 students (30 male and 18 female) was taught through CAIP while their counterparts in the control group which comprised 40 students (26 male and 14 female) was taught using lecture method. A 30-item animal physiology achievement test which was validated by experts and whose reliability coefficient of 0.85 was obtained was administered as pretest and post-test on both groups. Data gathered were analyzed using t-test statistics. Findings revealed that there was significant difference between the mean achievement scores of the two groups in favour of those taught with CAIP. Also, the package improved the achievement of both male and female students taught. It was therefore recommended among others that, computer animation instructional package should be adopted in secondary schools to complement lecture method of teaching in order to improve students' achievement in agricultural science.